A 1T2M memristor-based logic circuit and its applications. (February 2023) - Su, Bowen; Cai, Jueping; Zhang, Yuxin; Wang, Yiding; Wang, Shuaili; Wen, Kailin
Abstract: A 1T2M logic gate design inspired by MRL logic is presented in this paper and a variety of applications based on 1T2M units are promoted. The innovation of this topic is to use the non-volatile nature of memristors with the advantage of small area and volume to constitute a NOT logic with storage function for bridging the gap of memristor-based circuits in the design of NOT gates with the MRL structure instead of transistors in conventional inverters. 1T2M is used in the improved XOR/XNOR logic, and on this basis the combinational logic circuit is designed so as to adapt to more digital circuit, in which the consumption is reduced by the high proportion of memristor in circuit. The implementations of the 1T2M structure demonstrates that 1T2M cell makes an excellent contribution to reducing circuit area and consumption through multiple comparisons. Thus the way is paved for simulating the logic function of dendrites and implementing artificial neural networks at large scale.